FEATURES OF A COURSE OF THE INFECTION CAUSED BY A VIRUS OF HERPES OF THE 6TH TYPE AMONG CHILDREN OF EARLY AGE IN THE SETTING OF A ACUTE RESPIRATORY VIRAL INFECTION - N. V. Okolysheva; R. R. Klimova; E. V. Chichev; L. B. Kisteneva; N. A. Malishev; A. A. Kushch (LLC "Diagnostics and Vaccines", 2015)
We examined 95 children aged from 5 months till 3 years (middle age 1,7 ±1,1), who were admitted in children's infectious department of theClinicalInfectionsHospital№1 by diagnosis acute respiratory virus infection in the height of disease. Anti-genes of sharp respiratory viruses by the IF method, markers of HHV-6 type, and also a cytomegalovirus of the person (CMV) and Epstein-Barre's virus the ELISA methods and PTsR-rv are studied. Respiratory viruses are found among the hospitalized children in 46,3% of cases, from them paraflu (32,6%) in comparison with flu (9,5%) and a respiratornosintsitialny virus (4,2%), р < 0,05 statistically significantly is more often revealed. Markers of HHV are revealed at 73,7% of children. During the mixed infection HHV-6 markers are found in the vast majority of children (79,4%) in combination with this or that representative of Herpesviridae, is statistically significantly more often with CMV(16,8%), р < 0,05. DNA of HHV-6 is statistically significantly more often (41%) and with more viral load (53 400 copies/ml ) is revealed in a saliva in comparison with blood and urine. DNA of HHV-6 ina saliva statistically significantly is defined among the children visiting child care centers more often, than at unorganized children (72% against 40,4%, р = 0,0001) that testifies about a horizontal transmission of infection. It is observed that markers of HHV-6 are defined statistically significantly more often among children aged from 7 till 12 months (50%) and among children older by 1 year (49,2%) in comparison with children aged from 0 till 6 months (10%), р < 0,05. It is shown that among children of an early age the exanthema at HHV-6-of an infection is associated with presence of DNA of HHV-6 with high concentration (more than 120 000 copies/ml) in blood.